Design of a Mobile-Based Entrance Exam Test Application Using the Agile Method - Dandy Stevanus Tarigan (Jurnal Inovasi Informatika dan Bisnis Digital (JIIBD), 2026)
The rapid development of information technology has encouraged various educational institutions to innovate, including in the student admission selection process. The selection process, which is still conducted manually, often takes time, is inefficient, and prone to errors. Therefore, this study aims to design and develop a mobile-based entrance examination application that can be accessed flexibly by prospective students from anywhere. The methodology used in the development of this application is the Agile method, which allows the development process to be carried out iteratively and adaptively to changing user needs. The application is equipped with features such as question management, exam implementation, and automatic calculation of exam results. System testing was conducted using the black-box testing method to ensure that all functions run according to requirements. The results of this development show that the application can run well on the Android platform, providing convenience for administrators in managing questions and improving time efficiency in the assessment process. With this application, it is expected that the student admission selection process will become more effective, transparent, and easily accessible.